Construction and validation of the prosocial adolescent risk-taking questionnaire (PAR-Q) - Rebecca van Rijn; Paul A. M. van Lange; Lydia Krabbendam; Barbara R. Braams (Scientific Reports)
Abstract While negative risk-taking behavior in adolescents is a classic topic, extant research has long spent little attention to the positive aspects of adolescents’ development. One topic that started to gain more research focus is prosocial risk-taking behavior—defined as behavior where an individual takes a risk to help someone else. However, validated measures are still limitedly available. The goal of the study is to construct and validate a multifaceted measure to assess prosocial risk-taking in adolescents. A sample of 234 Dutch adolescents (149 girls) aged 14–17 filled in the unvalidated prosocial adolescent risk-taking questionnaire (PAR-Q) to perform iterative exploratory factor analyses to indicate initial factor structure. A separate data sample of 357 Dutch adolescents (208 girls) aged 14–17 filled in the PAR-Q to confirm this factor structure with iterative confirmatory factor analyses and additional questionnaires for convergent validity. In this sample, also test–retest reliability was assessed. The final two-factor structure, which represented Social and Material prosocial risk subscales, exhibited acceptable internal consistency and excellent test–retest reliability. The PAR-Q correlated positively with prosocial behaviors and empathy. The PAR-Q is a newly validated measure with adequate psychometric properties that can be used to gain more information on prosocial risk-taking behavior in adolescents.